(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
This article talks about the legal basis of the activities of internal affairs bodies of the Republic of Uzbekistan in 2016-2020. Based on historical data, the author studied and analyzed specific aspects of the legal basis of the activities of internal affairs bodies of the Republic of Uzbekistan in 2016-2020 on the basis of available scientific literature.